2013
DOI: 10.1016/j.meatsci.2012.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of cooked offal derived from free-range rams reared in South Africa

Abstract: Nutritional value of Dorper (n = 10) and Merino (n = 10) by-products were evaluated. Proximate composition differed between organs and breeds with Merino heart (68.9 g/100 g), spleen (77.2 g/100 g) and testicles (83.7 g/100 g) having higher moisture contents than their Dorper counterparts. Dorper brain (10.1 g/100 g), heart (15.2 g/100 g), spleen (20.4 g/100 g) and testicles (12.9 g/100 g) had higher protein contents than Merino. Dorper organs also tended to have a lower fat content. Amino acid and fatty acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 25 publications
3
49
0
2
Order By: Relevance
“…When SFAs and PUFAs are consumed together, their ratio (the P : S) is an important measure of the relative risk factor of the cholesterol content in a foodstuff [46]. Female and male quail meats consisted P : S ratio of 0.43 and 0.40, respectively (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…When SFAs and PUFAs are consumed together, their ratio (the P : S) is an important measure of the relative risk factor of the cholesterol content in a foodstuff [46]. Female and male quail meats consisted P : S ratio of 0.43 and 0.40, respectively (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…sociocultural traditions, religion, income, etc. Generally, offal is used in many countries as a cheap culinary raw material (Toldrá et al 2012, Hoffman et al 2013, Seong et al 2014. Currently, there is limited information available to consumers about the nutritional value of offal.…”
mentioning
confidence: 99%
“…It is relevant for customers who follow the principle of conscious nutrition (Tomović et al 2011, Seong et al 2014, Tomović et al 2016, Babicz et al 2018. It should be emphasised that offal is the main component of traditional products in many regions of the world, including Poland (Hoffman et al 2013). Therefore, investigations of the current nutritional value in edible slaughter by-products in comparison with the most widely consumed pig carcass elements are advisable.…”
mentioning
confidence: 99%
“…Hoffman et al [46] in their study also found a significant breed effect on the proximate composition of all the organs meat, with Merino sheep having higher fat content in liver, and tongue than Dorper sheep. However, Dorper brain, heart, kidney, spleen and testicles had higher protein contents than those of the Merino.…”
Section: Edible By-productsmentioning
confidence: 80%